Business factors related to manufacturing firms' performance - Stergios Vranakis; Prodromos Chatzoglou (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: The main goal is to understand the way many factors affect the investment decision making process and business performance.Design/methodology/approach: This study proposes a new conceptual framework for examining the reasons that manufacturing firms decide to invest on the acquisition of new machinery and equipment in order to improve their infrastructure. It incorporates various factors related to the internal business environment (quality management, investment decisions etc.) Findings and Originality/value: A new conceptual framework, establishing the relations between many factors, has been developed, allowing the determinants of adoption of many implications to be discussed and to relate them to the peculiarities of the Greek manufacturing industry. Originality/value: This study presents an overview of the impact of machinery and equipment investment on firm's performance, giving grasp for further research of the inter-organizational relationships that exist between them.
Keywords: 650; machinery & equipment investments; firm performance; just in time; total quality management; supply chain management; environmental management